The Effect of Shallot Extract as Natural Plant Growth Regulator and Cuttings Materials on The Growth of Water Apple (Syzygium aqueum l.) Stem Cuttings - Makrufah, Aliatul; Karno, Karno; Rosyida, Rosyida (Universitas PGRI Semarang, 2023)
The propagation of water apple by cuttings can meet the needs of the seeds in a short time and in large quantities. This study aimed to examine the effect of shallot extract as a natural plant growth regulator (PGR) and cutting material on the growth of water apple stem cuttings. The research was carried out from July to September 2022 at Greenhouse and the Physiology and Plant Breeding Laboratory, Faculty of Animal Husbandry and Agriculture, Diponegoro University. This study used a factorial Completely Randomized Design (CRD) with two factors. The first factor was the PGR concentration of shallots at four levels : K0 = 0%, K1 = 30%, K2 = 60%, and K3 = 90%. The second factor is the material of the water apple cuttings, with three levels: A1 = tip, A2 = middle, and A3 = base. The results of this study showed that the PGR concentration of shallots had significant effect on the age of shoots. The material of cuttings had a significant effect on age of shoots and the number of shoots. The natural growth regulator concentration of shallots 30% (v/v) in the shoots gave the best results for the growth of water apple cuttings